(untitled) - FARAH DIAN, NOVA (Jurnal Ilmu Manajemen (JIM), 2013)
Starbucks Corporation is a coffeehouse network of the United States are located in Seattle, Washington. Coffee shop today is not just a place to drink coffee, but a public space for socializing, gathering either for family, business, friendship or just to meet. Currently, the coffee shop has a more exclusive but with a more populist approach. The look and atmosphere of the coffee shop makes consumers not specifically come to enjoy coffee but tend to buy the concept of ambience and facilities provided by the coffee shop.This study aims to analyze and discuss the influence of the reference group and the atmosfir restoran on purchase decisions in Starbucks coffee shop.Techniques for collection data is questionnaire and technique analysis data using multiple linear regression analysis. The result showed that reference group and the atmosfir restoran influence give contribution of influenced on purchase decision. Keywords : Refference group, Resto Atmosphere, and Purchase decision